Lecture notes on design and analysis of breed comparison experiments - Rege, J.E.O. (International Livestock Centre for Africa, 1991)
Summarises the critical steps for designing a comprehensive breeding system. Breed (genotype) comparison and utilization are discussed with ref. to breeding policy, environment and management systems, genetic parameters, purebreds, F1 crosses, rotational crossing, and F2 and F3 generations of breed crosses. The part on analytical methods deals with computation of parameters, topocross evaluations, least-squares procedures, and presents three models that represents the analysis of data in which linebreds are not included.